Border-state abortions increased for Texas residents after House Bill 2 - Raifman, Sarah (Contraception, 2021)
OBJECTIVES: To assess changes in Texas-resident border-state abortions, medication abortions, and abortions ≥22 weeks from last menstrual period (LMP) before and after implementation of House Bill 2 (HB2) in November 2013 and before and after the US Supreme Court’s decision regarding HB2 in June 2016. STUDY DESIGN: We conducted an interrupted time series analysis using 2012–2017 data on Texas-resident abortions in Arkansas, Louisiana, Oklahoma, and New Mexico. Data on procedure type and gestational age were available only for abortions in New Mexico. RESULTS: Border states reported 762 Texas-resident abortions in 2012, 1,673 in 2014, and 1,475 in 2017. Texas-resident abortions in all border states nearly doubled following HB2’s implementation (incidence rate ratio [IRR]=1.92, 95% CI: 1.67–2.20). Border-state abortions then decreased by 19% after the 2016 US Supreme Court decision, compared to the period prior to the decision and after HB2’s implementation (IRR=0.81, 95% CI: 0.73–0.91). The proportion of Texas-resident abortions in New Mexico that were medication abortion increased from 5% to 20% (p<0.001) and the proportion that were ≥22 weeks from LMP decreased from 40% in 2012 to 23% in 2014 (p<0.001). Texas vital statistics undercounted annual out-of-state abortions, reporting only 13%-73% of abortions reported by border-state clinics during the study period. CONCLUSIONS: HB2 was associated with increases in border-state abortions for Texas residents, including in the number of those ≥22 weeks from LMP. Border-state abortions declined after the Supreme Court ruled HB2 unconstitutional yet remained higher than pre-HB2 levels. IMPLICATIONS STATEMENT: Abortion restrictions that severely curtail access may result in increases in travel out of state for care. Documenting out-of-state abortions is important for evaluating broader policy impacts and to prepare for future service disruptions. Texas residents may have more limited options for care if border states enact restrictive abortion laws.